FOREIGN EXPERIENCE OF COMMERCIAL BANKS PROVIDING REMOTE BANKING SERVICES - Tangriyev Izzat Raxmatullayevich (Modern American Journals, 2025)
New technologies in the banking system are changing the banking and financial system from today's perspective, and the appearance of traditional banking services is expected to change in the near future. Security is certainly a primary, pressing issue when it comes to providing remote banking services. Security features, such as advanced cryptography and human biometrics, help protect bank customers from fraud, and remote applications make it easier than ever for customers to complete their banking transactions without having to visit a bank branch. Below, we will consider how modern technologies are changing the way banks exchange information and manage money when they provide remote services.